2006
DOI: 10.1007/s00464-005-0117-6
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory response and bacterial dissemination afterlaparotomy and abdominal CO2 insufflation in a murine model of peritonitis

Abstract: Our results suggest that cavity insufflation with CO2 is a more effective method of access, inducing less bacterial dissemination and also a less intense inflammatory response. Cavity insufflation with CO2 may present a good option for the surgical treatment of patients with bacterial peritonitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 32 publications
1
14
0
1
Order By: Relevance
“…However, the effects of pneumoperitoneum on immune response, bacterial dissemination, and sepsis are controversial. The most investigated aspects are the type of gas and different levels of pressure employed in peritoneal insufflation [6,11,12] as well as the time duration of pneumoperitoneum. In this respect, a recent experimental study showed that, during peritonitis, CO 2 pneumoperitoneum applied at clinically standard pressures even for extended time intervals reduces the severity of sepsis and prolongs survival [3].…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of pneumoperitoneum on immune response, bacterial dissemination, and sepsis are controversial. The most investigated aspects are the type of gas and different levels of pressure employed in peritoneal insufflation [6,11,12] as well as the time duration of pneumoperitoneum. In this respect, a recent experimental study showed that, during peritonitis, CO 2 pneumoperitoneum applied at clinically standard pressures even for extended time intervals reduces the severity of sepsis and prolongs survival [3].…”
Section: Discussionmentioning
confidence: 99%
“…In a similar experiment, Pitombo and coworkers demonstrate, 18 h after bacterial inoculum into the peritoneum, a significant increase of CFU/mL for the laparotomy group compared with CO 2 and control groups [6]. In our study, the microbiological evaluation of peritoneal fluid collected after CLP and pneumoperitoneum revealed that CO 2 significantly reduced the number of colony forming units in this group of animals compared to the LS group.…”
Section: Discussionsupporting
confidence: 76%
“…Recently, we demonstrated that CO 2 pneumoperitoneum reduces inflammatory response by reducing early liver and lung interleukin (IL) 6 and tumor necrosis factor-alpha (TNF- α ) expression in cecal ligation and puncture rat model [4]. Other studies have reported that CO 2 insufflation could also influence intra-abdominal bacterial contamination in murine models of abdominal sepsis [5, 6]. In this regard, β -arrestins play a critical role as modulators of inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…The difference between the groups could not be explained because focusing on the bacterial behavior, we did not measure the kinetic determinations of the cytokine levels. There are various studies comparing cytokine levels in laparoscopy and laparotomy in the absence of infection, of which many show decreased inflammatory response in laparoscopy [18][19][20]. Further cytokine studies comparing the 2 techniques are needed on peritonitis models [15].…”
Section: Discussionmentioning
confidence: 99%